Minat Nasabah Terhadap Produk Profit And Loss Sharing Pada Perbankan Islam - Sibilang, Linne; Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 2 No.1, 2003 JBE UNKLAB, 2003)
This paper attempts to invesyigate the reason why mudarabo and musyaraka are not popular. Since these two instruments are designed to serve investement activities, they are critical elements to the development of Islamic banking and national development. We use risk and return mapping to analyze mudaraba and musyaraka position vis-a-vis conventional banking position. We argue that there is a mismatch of risk and return in both instruments. We also argue that there is a mismatch between customer’s perception of risk and return and bank’s profitability. We propose that islamic bank redefine both instruments’ position and attempt to change costumers’ perception on their tisk and return. This kind of analysis (positive analysis)in islamic economics is important to enrich theory of Islamic economy. We discuss venture capitalist. Vature capitalists offers profit-loss sharing, which is very similiar to that offered by mudaraba and musyaraka system. Venture capitalist, by its profit-loss sharing charakteristic, targets young and star-up companies. Since the risk of these companies is substantially higher than mature companies, conventional banks tend to avoid these companies. Thus, venture capitalist help serve young companies that later develop into big companies, that would otherwise disappear because of funding problem. In this way, venture capitalist help develop nations economy and society’s wealth. By providing comparison with venture capitalist we attempt to provide insight into what Islamic bank should position itself in financial market.